Voter Education: Strategy to Increase Voter Participation in Using Their Voting Rights - Bayu Karunia Putra; Azizatul Farhaini; Dinatul Aini; Siti Nurjannah; Noviana Noviana; M Ihya Ussarwan; M. Rizqi Alawi Al Ihsani; Iga Zuwi Annisa; Aripatun Hipzi; Isnaeni Isnaeni (Peneliti.net, 2023)
This article aims to find out strategies for increasing voter participation in exercising their voting rights. This topic is important and interesting, because the increase in voter participation has a great influence in conducting elections, especially when accompanied by socialization and voter education which become a strong foundation for building the level of voter participation in using their voting rights as well as possible. This research method is a type of research that uses a descriptive qualitative approach, where this method utilizes qualitative data and is described descriptively. Sources of data in the study were obtained through interviews, observation, and online media (Publish or Perish database, SINTA, and Goggle Scholar). Data collection and data analysis techniques in this study were using interview, observation, and online media techniques (Publish or Perish database, SINTA, and Goggle Scholar) which were carried out by researchers to collect, explore, and collect valid, complete, and relevant information related to the topic of the problem that is the object of research. The author finds that, related to this activity, it is very useful as a strategy to foster a high participatory attitude in using their voting rights as well as possible, because this activity is a step to encourage as an agent of change (agent of change), so that awareness of political rights, democracy, and community participation can be increased again.